Performance Analysis of Financial Statements on CV. SAM in Gowa District - Muhammad Asir; Siswati Rachman; Nur Fadny Yuliani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of the research is to determine the financial performance of CV. SAM in Gowa Regency is seen from the liquidity ratio, solvency ratio, activity ratio and profitability ratio. SAM in Gowa Regency with the use of financial ratio analysis. The data used in this study is primary data in the form of financial statement information consisting of Balance Sheet and Income Statements for the last three accounting periods, 2018, 2019 and 2020. The data collection techniques used in documentation research are financial statement data consisting of balance sheets and reports Profit and Loss for the 2018 Period, 2019, and 2020. The data analysis method used in this research is qualitative and quantitative analysis. Calculating financial ratios is then explained in informative sentences. The results show that the financial condition of CV. Gowa Regency SAM during 2018 to 2020 is classified as good. This is due to the ability and good management performance, especially in receivables turnover, the ability to achieve sales turnover targets, foresight to increase the stock of merchandise inventory.